Robust formation of nanoscale magnetic skyrmions in easy-plane anisotropy thin film multilayers with low damping - Flacke, Luis; Ahrens, Valentin; Mendisch, Simon; Korber, Lukas; Bottcher, Tobias; Meidinger, Elisabeth; Yaqoob, Misbah; Muller, Manuel; Liensberger, Lukas; Kakay, Attila; Becherer, Markus; Pirro, Philipp; et al. (Physical Review B, 2021)
We experimentally demonstrate the formation of room-temperature skyrmions with radii of about 25 nm in easy-plane anisotropy multilayers with an interfacial Dzyaloshinskii-Moriya interaction (DMI). We detect the formation of individual magnetic skyrmions by magnetic force microscopy and find that the skyrmions are stable in out-of-plane fields up to about 200 mT. We determine the interlayer exchange coupling as well as the strength of the interfacial DMI. Additionally, we investigate the dynamic microwave spin excitations by broadband magnetic resonance spectroscopy. From the uniform Kittel mode we determine the magnetic anisotropy and low damping . We also find clear magnetic resonance signatures in the nonuniform (skyrmion) state. Our findings demonstrate that skyrmions in easy-plane multilayers are promising for spin-dynamical applications.
CRIS-Team Scopus Importer:2023-03-27